An imaginary line? Decolonisation, bordering and borderscapes on the Ghana–Togo border. Issue 5 (11th May 2021) - Adotey, Edem
Abstract: Africa's inherited colonial borders have been central in debates on decolonisation for reasons that include challenges posed to African mobilities and identities, suggesting that there is a crisis of ideas about the border. This article draws on critical border studies (CBS) to examine the agency and negotiating capabilities of border residents using Leklebi and Wli, on the Ghana–Togo border, as case studies. How are discourses and practices of the border embedded in the contemporary everyday life of the borderland residents? What do their bordering practices reveal about their borderscapes? Are borderscapes being created or negotiated dependent on context? It argues that in these borderlands, borderscapes and bordering are conceived and expressed contextually not only through the lens of the postcolonial territorial border but also through the precolonial migration histories as well as precolonial concepts of political space. It contributes to border studies by highlighting the importance of historical and cultural factors in bordering and borderscapes. An understanding of such complexities may, in a significant way, help us to rethink or reconsider the arbitrariness of borders.